1999
DOI: 10.1046/j.1365-2141.1999.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activation in human acute leukaemias

Abstract: Summary. Plasminogen activation is implicated in solid tumour growth, invasion and metatastic spread. However, little is known about its role in leukaemia. We investigated the production by leukaemic cells of plasminogen activators [urokinase (uPA) and tissue-type PA (tPA)], cell surface receptor for uPA (uPAR) and PA inhibitors (PAI-1 and PAI-2). Leukaemic cells from 37 patients [26 with acute myeloid leukaemia (AML) and 11 with acute lymphoid leukaemia (ALL)] were analysed for mRNA content and enzymatic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…36,37 In leukemias, it has been shown that PAI-2 is up-regulated in M2 and M4 to M5 types and is thought to be responsible for the invasive phenotype of these cells. 23 Consistent with these observations we have also shown that hematopoietic cells forced to express ZNF198/FGFR1 also up-regulate PAI-2. In a report, PAI-2 was also shown to bind to the retinoblastoma (RB1) protein and protect it from degradation by an as yet unknown protease.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…36,37 In leukemias, it has been shown that PAI-2 is up-regulated in M2 and M4 to M5 types and is thought to be responsible for the invasive phenotype of these cells. 23 Consistent with these observations we have also shown that hematopoietic cells forced to express ZNF198/FGFR1 also up-regulate PAI-2. In a report, PAI-2 was also shown to bind to the retinoblastoma (RB1) protein and protect it from degradation by an as yet unknown protease.…”
Section: Discussionsupporting
confidence: 77%
“…23 This finding prompted us to focus further on the role of PAI-2 up-regulation in ZNF198/FGFR1 fusion kinase-expressing cells. RT-PCR and Western blot analyses were used to analyze HEK-293 cells which expressed GFP, ZNF198, or ZNF198/FGFR1.…”
Section: Analysis Of Pai-2 Expression In Znf198/fgfr1-expressing Cellsmentioning
confidence: 99%
“…Previous reports suggest that the secretion of PAs by myeloid cells is linked to their differentiation, tPA is being produced by normal myeloid progenitor cells whereas, uPA is produced by more mature myeloid cells (Vassalli et al. , 1991; Scherrer et al. , 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, uPAR mRNAwas also present in two cases of T-cell type ALL but not in any early B-type ALL cases. 112 Multiple myeloma is a B-cell malignancy, and the expression uPAR in myeloma cells varies in different reports. In myeloma cell lines and in patients with multiple myeloma, uPAR was found to be expressed using flow cytometry.…”
Section: K Leukemiamentioning
confidence: 99%